Flowmetry evolution in microvascular surgery: A systematic review. Issue 9 (September 2017) - Pafitanis, Georgios; Raveendran, Maria; Myers, Simon; Ghanem, Ali M.
Summary: This review aims to provide a summary of the flowmeter devices used in microvascular surgery and assesses their contribution to improving the clinical outcomes of free tissue transfer. Flowmeters are widely accepted as the standard method of intraoperative assessment of the patency of coronary vascular anastomoses, providing thresholds that predict outcome. There is limited evidence regarding the use of flow measurements in plastic surgery microvascular anastomoses; however, flowmetry appears to have some role in postoperative free flap monitoring and prevention of complications. Surgeons rely on subjective clinical robust findings (patency test) as proof of immediate flow. The current literature lacks evidence regarding an objective predictor tool used to evaluate adequate flow changes before and after microvascular anastomosis. An electronic literature search was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement by using the MEDLINE, EMBASE, and Cochrane databases. A combination of algorithms including "flowmeter, " "Doppler ultrasound, " "transit volume flow, " and "laser Doppler flowmeter" meshed with "microsurgery" was used to search for experimental and clinical studies that assess microvascular anastomoses by using a flowmeter device. A total of 718 peer-reviewed publications and 14 full-text articles described the use of microvascular flowmeters to determine anastomotic patency or free flap viability. Flowmeters are currently used to provide the qualitative assessment of microvascular anastomoses. It seems reasonable to expect flowmetry to provide quantitative values that can be used intraoperatively to predict both outcomes and the necessity for an on-table anastomosis revision; this may allow surgeons to better understand the other factors that predict failure by exclusion.